Investigating the difference in English language classroom anxiety between special programme and regular programme students at SMK Telok Mas / Nurul Iman Ahmad Bukhari - Ahmad Bukhari, Nurul Iman (2010)
This comparative study attempted to investigate the differences in English Language anxiety level between Form 3 Special Programme and Regular Programme students of Sekolah Menengah Kebangsaan Telok Mas, Malacca. The sample consisted of 154 Form 3 secondary school students, with 77 students in the Special Programme and 77 students in the Regular Programme. Horwitz's (1986) Foreign Language Classroom Anxiety Scale (FLCAS) was utilized in collecting the data about English Language anxiety among the students. Variables of English language anxiety like communication apprehension, fear of negative evaluation, test anxiety, and anxiety of English classes were examined. Descriptive analyses, one-way ANOVA and paired sample t-tests were used to conduct this comparison. The findings showed that there were no significant differences of overall English Language anxiety between Special Programme and Regular Programme students. As for the four anxiety variables, only test anxiety proved to have a significant difference between the two groups. Based on the findings, the conditions which influence high level of anxiety in the English classroom are speaking English in the classroom, possibility of embarrassment and rejection among peers, sitting and preparing for English tests, and students' negative perceptions of the English Language. Main implications derived from this study include utilizing the FLCAS in assessing students' anxiety level, and also to make the English classroom environment less intimidating and less stressful for learners by changing methods of teaching English in the classroom. For future research, it is recommended that for this topic, a qualitative approach be added to attain more detailed findings of students' perceptions on English language learning anxiety.